Drivers for human papillomavirus vaccination in Valencia (Spain) - Pedro Navarro-Illana; Esther Navarro-Illana; Rafael Vila-Candel; Javier Díez-Domingo (Elsevier, 2018)
Objective: To describe the drivers associated with HPV vaccination in adolescent girls and their parent's opinion on the vaccine. Methods: We conducted an observational and cross-sectional study on adolescent girls and their parents in Valencia (Spain), between September 2011 and June 2012. A consultation was made at a random sample of schools of the 14-year-old girls that should have received the vaccine in the free vaccination programme. We ran a personal survey on knowledge and attitudes regarding HPV infection and the vaccine. A binary logistic regression model was performed to determine which factors were most associated with vaccination. Results: The survey was run on a binomial of 1,278 girls/mothers in 31 schools, to which 833 girls and their mothers responded (64.0%). The factors associated with vaccination were: country of origin of the families (adjusted OR [aOR]: 0.49; 95% confidence interval [95%CI]: 0.24-0.98), civil status of the parents (aOR: 0.33; 95%CI: 0.13-0.81), knowledge/beliefs about the vaccine when the source of information was the nurse (aOR: 1.83; 95%CI: 1.01-3.35), information source about the vaccine (aOR: 2.32; 95%CI: 1.37-3.92), preventive health centre visits (aOR: 2.1; 95%CI: 1.10-4.07), and nurse advice (aOR: 6.6; 95%CI: 3.19-13.56). Conclusions: The main factor associated with HPV vaccination was the advice of health professionals. Therefore, the most effective interventions to improve vaccination coverage should focus on health professionals. Resumen: Objetivo: Describir qué factores se asocian a la vacunación contra el virus del papiloma humano (VPH) en adolescentes y la opinión de sus padres/madres sobre dicha vacuna. Métodos: Se llevó a cabo un estudio observacional y transversal en chicas adolescentes y sus progenitores en Valencia (España), entre septiembre de 2011 y junio de 2012. Se realizaron consultas a las niñas de 14 años que tendrían que haber sido vacunadas dentro del programa de vacunación gratuita, en una muestra aleatoria de colegios. Se preguntó sobre conocimientos y actitud respecto a la infección por el VPH y la vacuna, mediante entrevista personal. Se llevó a cabo un modelo de regresión logística binaria para determinar qué factores estaban más asociados con la vacunación. Resultados: Se entrevistó a 1278 binomios chica/madre, con una tasa de respuesta del 64,0% (833). Los factores asociados a la vacunación fueron el país de origen de las familias (odds ratio ajustada [ORa]: 0,49; intervalo de confianza del 95% [IC95%]: 0,24-0,98), el estado civil de los progenitores (ORa: 0,33; IC95%: 0,13-0,81), los conocimientos/creencias sobre la vacuna cuando la principal fuente de información fue la enfermera (ORa: 1,83; IC95%: 1,01-3,35), la fuente de información sobre la vacuna (ORa: 2,32; IC95%: 1,37-3,92), las visitas preventivas al centro de salud (ORa: 2,12; IC95%: 1,10-4,07) y el consejo de la enfermera (ORa: 6,57; IC95%: 3,19-13,56). Conclusiones: El principal factor asociado a la vacuna del VPH fue el consejo del personal sanitario, por lo que las intervenciones para aumentar la cobertura vacunal deben centrarse en este colectivo. Keywords: Human papillomavirus, Vaccines, Drivers, Attitudes, Nurse, Palabras clave: Virus del papiloma humano, Vacuna, Factores asociados, Actitud, Enfermería